'I'll just say two words ‐ "East Timor"': An interview with Norm Breyfogle1. Issue 2 (1st November 2019) - Klaehn, Jeffery
AbstractNorm Breyfogle (27 February 1960‐24 September 2018) is widely recognized for his six years (1987‐93) spent illustrating various Batman titles for DC Comics, most notably Detective Comics, Batman and Batman: Shadow of the Bat. He also illustrated several prestige edition one-shots set within the Batman narrative universe, including Batman: Birth of the Demon (1992), which he hand-painted, and the 'Elseworlds' stories, Batman: Holy Terror (1991), Batman: The Abduction (1998) and Batman: Dreamland (2000). In this interview, undertaken in 2007, he discusses his approach to cover design and interior art; the comic industry; how he came to work on Batman; his collaborations with writer Alan Grant; reflections on the character of Anarky; details on an unpublished three issue Anarky storyline involving East Timor and US arms sales to Indonesia; how Batman has changed over the decades; as well as his thoughts on how Jim Aparo, Marshall Rogers and Frank Miller drew Batman.